Determinants of International Arms Control Ratification - Agnes Brender (University of Hamburg, Institute of Law and Economics (ILE), 2018)
The paper analyses the determinants of ratification of international treaties concerning arms control. It theorizes that the ratification of an arms control treaty serves as a signal of a country's intention to avoid arms races and wars. I argue that fast growing countries have a special incentive to send that signal in order to avoid aggression from declining powers. Also, democracies are hypothesised to support the underlying humanitarian norms of arms control treaties and therefore ratify arms control agreements more often. The theory is tested by panel ordered logit regression of the number of treaties ratified by a country and with panel logit estimation of treaty ratification. The data cover 186 countries over the period of 1975-2010. Results support the theory and suggest that especially treaties where compliance can be considered as cheap are ratified more often.
Keywords: F53; K33; H56; 320; Arms control; International Treaties; International Humanitarian Law